Performance improvement of mode division multiplexing free space optical communication system through various atmospheric conditions with a decision feedback equalizer. Issue 1 (31st December 2022) - Almogahed, Abdullah; Amphawan, Angela; Mohammed, Fathey; Alawadhi, Abdulwadood
Abstract: Free space optics (FSO) systems use the atmosphere as a propagation medium. However, a common problem is atmospheric turbulence, including fog, rain, and haze that emerges between the transmitter and the receiver from time to time. These adverse weather conditions impose power loss on the optical signal, producing distortion and degrading bit error rate (BER) and throughput. To reduce the effect of atmospheric turbulence, this paper proposes a decision feedback equalizer (DFE) with minimum mean square error (MMSE) in mode division multiplexing (MDM) for the FSO system. The DFE with varying tap counts is investigated. The MMSE algorithm is utilized to optimize both the feedforward and feedback filter coefficients of the DFE. The proposed system consists of four parallel 2.5 Gbps channels that use Hermite-Gaussian (HG) modes. The results show that the DFE equalization scheme successfully transmits 10 Gbps over 40 m, 800 m, 1400 m, and 2 km in medium fog, medium rain, medium haze, and clear weather. Performance is analyzed in terms of BER and eye diagrams and compared with the traditional model. Based on BER and eye diagram results, DFE improves the outdoor FSO system immunity to distortion in medium fog, medium haze, medium rain, and clear weather while maintaining high throughput and desired low BER.